Kinship System and Customary Government of the Waropen Indigenous Community - Tanati, Daniel (PT. Multidisciplinary Press Indonesia, 2025)
This study aims to determine the kinship system and customary government of the Waropen indigenous community. The research method used is empirical by observing the reality that occurs in the field. The results of this study reveal that the Waropen indigenous community recognizes a local kinship group called